Gut Metabolism of Sugars: Formation of Glycotoxins and Their Intestinal Absorption - Tamaeh Monteiro-Alfredo; Paulo Matafome (Diabetology, 2022)
Glycotoxins include the group of advanced glycation end-products (AGEs) and their precursors, most of them highly reactive intermediary compounds of sugar metabolism. Glycotoxins and products of the Maillard reaction are present in high concentrations in foods rich in sugars and processed at high temperatures and are often associated with the flavour of the food. Proteins undergoing this type of molecular modification are targets for gut peptidases and may be absorbed into circulation. AGEs are associated with the toxic effects of glucose in diabetic patients, and some studies have shown that they also contribute to metabolically unhealthy obesity and prediabetes development. Restriction of dietary glycotoxins was shown to improve insulin resistance in humans. However, the real contribution of dietary AGEs to such mechanisms is still not understood. This review summarizes the current knowledge about glycotoxin formation from dietary sugars, their digestion throughout the gastrointestinal system, and the mechanisms of their intestinal absorption.